Divisional Livelihood Development Plans (RADA Livelihood Unit : ILO-IRTAP, 2006)
Livelihood Unit of the Reconstruction and Development Agency, Sri Lanka and the Income Recovery Technical Assistance Programme of the International Labour Organization facilitated the development of Divisional Livelihood Development Plans in Sri Lanka.